Effect of the parafunctional occlusal loading and crown height on stress distribution - Torcato, Leonardo Bueno [UNESP]; Pellizzer, Eduardo Piza [UNESP]; Verri, Fellippo Ramos [UNESP]; Falcón-Antenucci, Rosse Mary [UNESP]; Batista, Victor Eduardo de Souza [UNESP]; Lopes, Leonardo Ferreira de Toledo Piza [UNESP] (FapUNIFESP (SciELO), 2014)
The aim of this study was to assess, by the three-dimensional finite element method, the influence of crown-to-implant ratio and parafunctional occlusal loading on stress distribution in single external hexagon implant-supported prosthesis. Computer-aided design software was used to confection three models. Each model was composed of a block bone and an external hexagon implant (5x10.0 mm) with screw-retained implant prostheses, varying the height crown: 10, 12.5 and 15 mm. Finite element analysis software was used to generate the finite element mesh and to establish the loading and boundary conditions. Normal (200 N axial and 100 N oblique load) and parafunctional forces (1,000 N axial and 500 N oblique load) were applied. The results were visualized by von Mises and maximum principal stress. In comparison with the normal occlusal force, the parafunctional occlusal force induced an increase in stress concentration and magnitude on implant (platform and first threads) and screw (neck). The cortical bone showed the highest tensile stress under parafunctional force (oblique load). The stress concentration increased as the crown height increased. It was concluded that: increasing the C/I increased stress concentration in both implant components and cortical bone; parafunctional loading increased between 4-5 times the value of stresses in bone tissue compared with functional loading; the type of loading variation factor is more influential than the crown-to-implant factor.